“The Destruction of a Legacy”: Agenda Setting and the Bill Cosby Sexual Assault Allegations - Terán, Larissa; Emmers-Sommer, Tara M. (Sexuality & Culture, 2018)
Utilizing agenda setting theory, this study investigates the Bill Cosby sexual assault allegation scandal and how the scandal is framed by the media. In order to examine if and how varied networks reported differently on the Cosby scandal, sixty articles from three, distinct networks (CNN, FOX News, E!) were analyzed and coded under seven different categories. Results demonstrate a significant difference among the analyzed networks and media frames most reported in the sample for this study. Although all networks address Cosby’s rise and fall of an American hero, agendas set and story frames presented varied. Specifically, CNN highlighted victims’/survivors’ powerful voice whereas E! and FOX News highlighted Cosby’s support from the black community, celebrities and co-stars. Additional results, discussion and future directions follow.
Keywords: Agenda setting theory; Bill Cosby; Mediated communication; Scandal; Sexual assault; Sophie-Anne

Enquête sur le portrait sociodémographique et l’égalité homme-femme chez les créatrices et créateurs d’humour au Québec – Sommaire 2018-2: Données sur la perception de l’égalité entre les femmes et les hommes - Paré, Christelle; Brouard, François (Groupe de recherche sur l’industrie de l’humour (GRIH), SCSE/CSES, Sprott Centre for Social Enterprises / Centre Sprott pour les entreprises sociales (SCSE/CSES), Université Carleton, 2018)
Keywords: Bibliographie; Humour; Nettoyer; Sophie-Anne; Types de VACS